Twin liquid crystals and segmented thermotropic polyesters containing azobenzene?effect of spacer length on LC properties - Nardele, Chinmay G.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
We report systematic studies on a homologous series of twin liquid crystalline (LC) molecules based on phenyl and naphthyl azobenzene (PnP and NpnNp) as well as segmented copolyesters based on them. The twin series had the structure azobenzene–oligooxyethylene–azobenzene, where the ethyleneoxy length was varied from 2 to 6 units. The LC properties of the twin series depended on the chemical structure of the azochromophore and also the length of the central oligooxyethylene segment. The PnP series exhibited smectic LC properties for n > three oligooxyethylene units. Conversely, NpnNp series exhibited spherulitic phases only for the shortest member –Np2Np. One non-LC short spacer twin (P2P) and one LC long spacer twin (P6P) were incorporated as part of a main chain polyester composed of fully aliphatic segments of sebacate and di or tetraethylene glycol (DEG/TEG) units by melt polycondensation. Non-LC P2P formed LC polymers even at low (5 mol %) incorporation in DEG-based copolymers, whereas the LC-P6P could do so only at 30 mol % incorporation. The LC properties of the twin molecules as well as copolymers were studied using differential scanning calorimetry, polarized light microscopy (PLM) along with variable temperature wide angle X-ray diffraction. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012